Verzierte Keramik von Hoyas del Castillo, Pajaroncillo (Cuenca), Schnitt 4 - Ulreich, Hermann; Negrete Martínez, María Antonia; Puch Ramírez, Elisa (Madrider Mitteilungen, 2021)
Deutsche Zusammenfassung folgt.